Trend of adherence to iron supplementation during pregnancy among Ethiopian women based on Ethiopian demographic and health surveys: A Multivariable decomposition analysis - Delie, Amare Mebrat; Gezie, Lemma Derseh; Gebeyehu, Asaye Alamneh; Tarekegn, Gebrekidan Ewnetu; Muche, Achenef Asmamaw (Frontiers in Nutrition, 2022)
Background Iron deficiency is one of the significant factors of anemia during pregnancy. Iron supplementation is the main method of prevention and control of iron deficiency anemia, and its effectiveness depends on adherence to the iron supplementation. Methods This study was based on a secondary analysis of 2005, 2011, and 2016 EDHS data. After the data was weighted using sampling weight, 696, 1,282, and 3,096 in 2005, 2011, and 2016 EDHS data, respectively, were used for the final analysis. The data were edited, cleaned, coded, managed, and analyzed using StataCorp version 16 software. A logit-based multivariable decomposition analysis was used to identify variables significantly associated with the change in the adherence level during pregnancy. Results Adherence levels increased from 1.1% (95% CI; 0.4, 2.7) in 2005 EDHS to 12.4% (95% CI; 10.9, 14.1) in 2016 EDHS. About 30.9% of the overall change in the adherence level to iron supplement use during pregnancy was due to the difference in women's sociodemographic-related variables. After adjusting for these compositional changes, ~69.1% of the change in the adherence level was because of the difference in the coefficients (behavior-related variables). Among the behavioral characteristics, women's age-group, rich wealth index, and secondary and above-secondary educational status of their husbands had a statistically significant effect on the positive change in the adherence level of pregnant mothers. Conclusion The adherence level to iron supplement use during pregnancy has increased significantly over the last decade in Ethiopia. Both the compositional and behavioral characteristics of women play a major role in the increasing trend of adherence levels.